Explore Westonci.ca, the leading Q&A site where experts provide accurate and helpful answers to all your questions. Ask your questions and receive precise answers from experienced professionals across different disciplines. Our platform provides a seamless experience for finding reliable answers from a network of experienced professionals.
Sagot :
Answer:
a⁴ + b⁴ = 433
Step-by-step explanation:
[tex]$\begin{aligned}(a+b)^4 & =a^4+4 a^3 b+6 a^2 b^2+4 a b^3+b^4 \\ & =a^4+b^4+6(a b)^2+a^2 \times 4 a b+b^2 \times 4 a b \\ & =a^4+b^4+6(a b)^2+4 a b \times\left(a^2+b^2\right) \\ & =4^4+b^4+6(a b)^2+4 a b \times\left[(a+b)^2-2 a b\right] \\ & =a^4+4^4+6 \times 2^2+4 \times 2 \times\left[5^2-2 \times 2\right] \\ & =a^4+b^4+24+8 \times[25-4] \\ & =a^4+b^4+24+8 \times 21 \\ = & a^4+b^4+192\end{aligned}$[/tex]
Since a+b=5 ,then we get this equation :
5⁴ = a⁴ + b⁴ + 168
then
a⁴ + b⁴ = 5⁴ - 192
= 625 - 192
= 433
Thank you for visiting. Our goal is to provide the most accurate answers for all your informational needs. Come back soon. Thank you for visiting. Our goal is to provide the most accurate answers for all your informational needs. Come back soon. Westonci.ca is your go-to source for reliable answers. Return soon for more expert insights.